Analisis EVA dan MVA sebagai Metode Penilaian Kinerja Keuangan pada PT Indofood Sukses Makmur Tahun 2021- 2024 - Lailatus Sa’adah; Wiwin Ananda Dwi Agustin; Ummi Charisma Alfi Ulul Azmi; Diyas Angga Kurniwan; Achmad Aji Bayu Pamungkas (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to analyze the assessment of the company's financial performance using the EVA (Economic Value Added) and MVA (Market Value Added) methods in PT Indofood Sukses Makmur Tbk for the 2021-2024 period. The results show that the company's ability to create economic value is not stable when measured by the EVA method, where in 2021 and 2023 EVA is positive, while in 2022 and 2024 EVA is negative. This shows that there are internal challenges that affect operational efficiency and capital management. Meanwhile, the company's MVA has been positive from 2021 to 2023 and increased in 2024, indicating that market perception of the company's outlook remains good. Overall, the study concludes that although Indofood faces internal dynamics that affect its economic performance in a volatile manner, the market still gives a positive appreciation. The fluctuations of EVA reflect the company's need to improve the consistency of economic value creation, while the high MVA confirms that investor confidence in the company's growth potential and long-term strategy remains strong and stable.